Religious Experience and Memory Retrieval: A Memory Studies Reading of Joseph Smith’s "First Vision" Accounts - Duffau, Céline (Journal of the American Academy of Religion, 2025)
Using as a model the primary accounts of the visionary experience of Joseph Smith (founder of The Church of Jesus Christ of Latter-day Saints), this article argues that multiple narratives of the same experience, religious or not, reveal how the mind processes memory over time. To that end, the article points to parallels shown in the retrieval of the 9/11 events and mobilizes the disciplines of neuroscience, psychology, and history to explain memory processes and illustrate how decompartmentalization between academic disciplines provides a better understanding of those processes. Beyond Smith and religion, the article concludes with the proposition that one’s reaction toward a version of a retrieved memory is influenced more by a subjective interpretation of and rapport with events, experiences, or narratives than by an entirely rational and objective understanding of the inherently unstable nature of memory.